Haimovici's vascular surgery. - Haimovici, Henry, 1907-2001.; Ascher, Enrico (Chichester, West Sussex : Wiley-Blackwell, 2012)
To improve the diagnosis and management of patients with vascular disease turn to the most authoritative and trusted reference for 36 years and counting ... The role of the vascular surgeon has evolved. Vascular surgeons now perform minimally invasive vascular procedures and provide comprehensive care in addition to open surgery. Haimovici's Vascular Surgery, now in its 6th edition, has been extensively updated to provide you with: Expert perspectives on how the vascular surgery field has evolved so you continue to stay on the lead.
pt. 1. Vascular imaging techniques and physiologic testing -- pt. 2. Basic science in vascular diseases -- pt. 3. Basic open vascular techniques -- pt. 4. Open surgical exposure of arteries -- pt. 5. Cerebrovascular insufficiency -- pt. 6. Aortic and iliac aneurysms -- pt. 7. Visceral vessels -- pt. 8. Lower extremity occlusive and non-occlusive arterial disease -- pt. 9. Vascular trauma -- pt. 10. Upper extremity vascular disease -- pt. 11. Arterial-venous malformation, access for hemodialysis and portal hypertension -- pt. 12. Venous and lymphatic disorders -- pt. 13. Amputations and rehabilitation.
Includes bibliographical references and index.
Print version record.
Keywords: Blood-vessels -- Surgery; Vascular Surgical Procedures; Vascular Diseases -- diagnosis; Vascular Diseases -- surgery; MEDICAL -- Surgery -- Vascular; Blood-vessels -- Surgery; Electronic books; Electronic books